2007
DOI: 10.1002/hed.20613
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pleomorphic adenoma of the parotid gland: Analysis of 108 consecutive patients

Abstract: Surgery for recurrent parotid pleomorphic adenoma has a high rate of facial nerve morbidity. The chance of rerecurrence is high. Extended parotidectomy seems to be the best approach for the reoperation to reduce the risk of rerecurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
102
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 31 publications
3
102
1
5
Order By: Relevance
“…Various treatment modalities have been reported, ranging from totally untreated patients to radical parotidectomies, in which the facial nerve branches are sacrificed, and adjuvant radiotherapy applied (4,7,(10)(11)(12). In our study, our approach to recurrent pleomorphic adenomas was discussed with review of the literature by discussing the clinical and surgical characteristics and follow-up results of 11 patients who had recurrence at an average of 11.9 years after the first surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various treatment modalities have been reported, ranging from totally untreated patients to radical parotidectomies, in which the facial nerve branches are sacrificed, and adjuvant radiotherapy applied (4,7,(10)(11)(12). In our study, our approach to recurrent pleomorphic adenomas was discussed with review of the literature by discussing the clinical and surgical characteristics and follow-up results of 11 patients who had recurrence at an average of 11.9 years after the first surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The first hypothesis regarding recurrent pleomorphic adenomas was first asserted by Patey and Thackray (6) in the 1950s and is associated with finger-like extensions, i.e., pseudopods, which are microscopically found protruding from the tumor pseudocapsule. It is believed that surgeries applied close to the pseudocapsule structure of the tumor increase the risk of recurrence by causing insufficient resection of the microscopic extensions, i.e., pseudopods, protruding from the tumor pseudocapsule (7). Another reason is tumor seeding, which is common in the surgical field, after opening the pseudocapsule structure of the tumor during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Makeieff et al have determined malignant transformation in 10 of 62 patients they had operated for recurrent pleomorphic adenoma (13). Wittekindt et al, on the other hand, do not report any malignant transformations in 108 patients undergoing surgery for recurrence (9). The study at the University of Florida reports malignant transformation in 2 of the 7 patients who formerly underwent adjuvant RT for recurrent pleomorphic adenoma with further recurrence after RT (8).…”
mentioning
confidence: 97%
“…In their study conducted on 108 recurrent pleomorphic adenoma patients, Wittekindt et al have found single recurrence in 32 and multiple recurrence in 56 patients (9). In a 25-patient study at the University of Florida, 68% of the patients have failed to be treated until the fourth surgical intervention while those who received RT have responded better to local control (8).…”
mentioning
confidence: 99%
“…The first recurrence has been reported twenty years after initial treatment and facial palsy complicates up to a third of patients undergoing surgery, although it is frequently temporary. [2][3][4] However, surgery in recurrence carries a higher risk of facial nerve injury, 5 which is more likely to impact on the group who did not receive post-operative radiotherapy. Moreover, pleomorphic adenoma (PA) recurrence can involve the skull base or old scars making adequate salvage surgery difficult and often requiring loco-regional reconstruction adding a layer of complexity and surgical morbidity.…”
mentioning
confidence: 99%